Effects of a Dipeptidyl Peptidase 4 Inhibitor Sitagliptin on Glycemic Control and Lipoprotein Metabolism in Patients with Type 2 Diabetes Mellitus (GLORIA Trial) - Masuda, Daisaku (J Atheroscler Thromb, 2018)
Aim: The morbidity of cardiovascular disease in patients with type 2 diabetes mellitus (DM) deteriorates in combination with dyslipidemia. The accumulation of remnant lipoproteins in patients with fasting and postprandial hypertriglyceridemia is highly atherogenic. The current study investigated whether the dipeptidyl peptidase-4 inhibitor sitagliptin ameliorates dyslipidemia and hyperglycemia. Methods: We enrolled 38 patients with type 2 DM (20 males and 18 females, 65.7 ± 9.9 years old, HbA1c levels < 8.4%), and all patients gave written informed consent. Sitagliptin (50 mg/day) was added to current antidiabetic treatments and increased to 100 mg/day to achieve low HbA1c levels (< 7.4%). Glucose and lipoprotein metabolism profiles were analyzed at 0, 4, and 12 weeks after sitagliptin administration. Results: Sitagliptin significantly decreased fasting levels of triglyceride (TG) (161 ± 90 vs. 130 ± 66 mg/dl, p < 0.01) and non-HDL-C (129 ± 29 vs. 116 ± 20 mg/dl, p < 0.01) in combination with glucose (150 ± 47 vs. 129 ± 27 mg/dl, p < 0.01) and HbA1c (7.1 ± 0.6 vs. 6.6 ± 0.7 mg/dl, p < 0.001). Sitagliptin also significantly decreased the fasting levels of apolipoprotein (apo) B-48 (7.8 ± 6.7 vs. 5.6 ± 4.0 µg/ml, p < 0.01), remnant lipoprotein cholesterol (15.3 ± 9.5 vs. 12.0 ± 7.9 mg/dl, p < 0.05) and other apolipoproteins, such as apoB, apoC-II, apoC-III, and apoE. Analyses of the lipoprotein profiles of fasting sera revealed that sitagliptin significantly decreased cholesterol and TG levels of lipoprotein fractions in the size of very low density lipoprotein and low density lipoprotein. Conclusions: These findings indicated that sitagliptin administration ameliorated the lipid and lipoprotein profiles in patients with diabetes, which may be due to the decrease in atherogenic remnant lipoproteins (UMIN#000013218). Abbreviations: apo: apolipoprotein ASCVD: atherosclerotic cardiovascular disease CHD: coronary heart disease CLEIA: chemiluminescence enzyme immunoassay CM: Chylomicron DPP-4: dipeptidyl peptidase-4 FFAs: free fatty acids HPLC: high-performance liquid chromatography IMT: intima-media thickness LDL: low-density lipoprotein LPL: lipoprotein lipase PHTG: postprandial hypertriglyceridemia RemL-C: remnant lipoprotein cholesterol RLP-C: remnant-like particle cholesterol TG: triglyceride TRL: triglyceride-rich lipoprotein VLDL: very low density lipoprotein